TimeBanking: towards a co-produced solution for power and money issues in inclusive research. Issue 4 (4th July 2017) - Nind, Melanie; Armstrong, Alan; Cansdale, Mal; Collis, Anne; Hooper, Clare; Parsons, Sarah; Power, Andrew
Abstract: This paper explores the potential of an online TimeBank for inclusive research to address some of the challenges related to the unequal distribution of power and money for researchers within and outside the academy working in collaboration. The problem, the concept of TimeBanking, and the relationship of TimeBanking to inclusive research principles are explained. The case is made for developing an online TimeBank for inclusive research, and an account is given of initial co-production of a prototype by an English interdisciplinary academic team and a Welsh workers cooperative set up and run by people with and without learning disabilities aiming to make public life more inclusive. The paper concludes that, while the concept is some way from becoming a reality, a hybrid digital-physical TimeBank, if accessible and flexible enough to attract usage, has potential for supporting democratised, inclusive research in practice.